2017
DOI: 10.1615/critrevimmunol.v37.i2-6.10
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Selection on the Major Histocompatibility Complex

Abstract: Only natural selection can account for the extreme genetic diversity of genes of the major histocompatibility complex (MHC). Although the structure and function of classic MHC genes is well understood at the molecular and cellular levels, there is controversy about how MHC diversity is selectively maintained. The diversifying selection can be driven by pathogen interactions and inbreeding avoidance mechanisms. Pathogen-driven selection can maintain MHC polymorphism based on heterozygote advantage or frequency-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(89 citation statements)
references
References 0 publications
2
86
1
Order By: Relevance
“…These findings support the hypothesis that mate choice favours an additive genetic benefit to offspring (Apanius et al 1997). Such choice has also been reported for female birds (Ekblom et al 2004) and fish (Eizaguirre et al 2009) but contrasts with the results of our earlier analyses, which found no effect of particular MHC supertypes on which male sired an offspring, providing no support for the hypothesis that females choose for specific MHC genotypes in males.…”
Section: Mate-guarding and Specific Mhc Genotypescontrasting
confidence: 57%
See 2 more Smart Citations
“…These findings support the hypothesis that mate choice favours an additive genetic benefit to offspring (Apanius et al 1997). Such choice has also been reported for female birds (Ekblom et al 2004) and fish (Eizaguirre et al 2009) but contrasts with the results of our earlier analyses, which found no effect of particular MHC supertypes on which male sired an offspring, providing no support for the hypothesis that females choose for specific MHC genotypes in males.…”
Section: Mate-guarding and Specific Mhc Genotypescontrasting
confidence: 57%
“…Thus, it appears that female mandrills choose MHC-diverse males, but that male mate-guarding is not biased towards MHC-diverse females. The reasons underlying mate choice for MHC-diversity are as yet unclear, but choice for an MHC-diverse mate may maximise offspring heterozygosity without reference to the chooser's own genotype (Reusch et al 2001), or increase the chance of offspring inheriting rare, beneficial alleles (Apanius et al 1997). The explanation for the possible sex differences is also unclear, but it is possible that males have no way of detecting MHC diversity in females, as female odour does not reflect MHC diversity, although male odour does (Setchell et al 2011).…”
Section: Mate-guarding and Mhc-diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious diseases are a major selective pressure; [15][16][17][18] and genes involved in the immune response are the most numerous and diverse in the human genome; 19 reflecting the evolutionary advantages of a diverse immunological response to a wide range of infectious pathogens. 20 …”
Section: Introductionmentioning
confidence: 99%
“…(Clarke, 1979) The genes of the major histocompatibility complex (MHC) appear to be the most polymorphic loci in vertebrates, and explaining how natural selection maintains such genetic diversity ('population allelic richness') is a major unsolved problem in evolutionary biology. There is accumulating evidence that MHC polymorphisms are maintained by balancing selection (Apanius et al, 1997;Spurgin and Richardson, 2010); however, the nature of this selection is still unclear. MHC genes encode cell-surface glycoproteins (class I and II molecules) that present peptide antigens to T cells, and thereby play an important role in the development of the T cell receptor (TCR) repertoire, immunological self/non-self recognition, and resistance to pathogens and parasites.…”
Section: Introductionmentioning
confidence: 99%